Electrochemically Synthesized Gold Nanoparticles Using Gold and Copper Electrodes - Ismira Wahyu Lestari Lewa; Meifina; Isnaeni (Jurnal Sains Materi Indonesia, 2023)
Gold nanoparticle is one of the interesting metallic nanoparticles that can be applied to various applications due to promising plasmon effect. Gold nanoparticles are usually synthesized from gold salts using chemical procedure to precisely control of their sizes and shapes. However, gold salt is expensive and the synthesis requirement and procedure are complicated. It is a challenge to produce gold nanoparticles using cheap, rapid, simple and massive method. Electrochemical is one of the simple procedures to synthesize gold nanoparticles; however, the utilization of platinum electrode, which is expensive, become disadvantage. In this work, we utilized copper plate to replace platinum electrode in order to synthesize gold nanoparticles. We also varied electrolyte, stabilizer, ambient temperature and injection current to study their effects on absorbance spectra of synthesized gold nanoparticles. We found that ambient temperature and injection current significantly affected shape of gold nanoparticles. Surprisingly, combination of salt-glucose or stabilizer-glucose was enough to synthesize gold nanoparticles. This work brings a simple and cheap technique for massive production of gold nanoparticles for various applications